Students’ Perception on The Use of Kahoots! as An Ice Breaking Medium in Learning English - Amalia Zatil Riski; Syarifuddin Dollah; Sultan Baa (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study investigates students' perceptions on the use of Kahoot! as a media in icebreaker sessions in English subjects. The independent variable in this study is Kahoot! as an ice breaking media, while the dependent variable is students' perceptions on the use of Kahoot! in icebreaker sessions. The population in this study was 30 students of class VIII B from UPT SPF SMPN 13 Makassar. This study used a mix-method research method with questionnaires and interviews as research instruments. The questionnaire was given to all students with open-ended questions, while in-depth interviews provided students' perceptions to support and add to the results of the questionnaire. The findings of this study reveal that students have positive perception on to use Kahoot! as an icebreaker medium in learning English.